RESEARCH OF ENERGY CONSUMPTION IN THE TRANSPORTATION OF OIL THROUGH MAIN OIL PIPELINES - Grudz, V. Ya.; Grudz, Ya. V.; Bolonnyi V. Т.; Malyutin, R. Yu.; Sadlivskyi, V. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2024)
The conducted studies relate to the structure of hydraulic energy losses during the transportation of oil or oil products through main pipelines. Based on the general laws of movement of a liquid continuous medium in pipes, it is advisable to divide the total energy losses into hydraulic losses due to viscous friction, gravitational energy losses, inertial energy losses, and Coriolis energy losses associated with the uneven distribution of the speeds of the moving medium along the cross section of the flow. The well-known mathematical model of the process of movement of a continuous medium consists of the momentum equation of the fluid flow, the continuity equation, and the energy equation. The first of the listed equations expresses d’Alembert’s principle to the system of forces acting on the fluid flow; the second represents the law of conservation of mass in a liquid flow, the third – the law of energy dissipation. Relying on the momentum equation, dependencies were obtained for estimating the value of each type of energy loss in the fluid flow. To find the numerical value of each type of energy loss, information on the modes of operation of the main gas pipeline system "Druzhba" on the western sections of the route over a long period was used. As a result, the indicated types of energy losses with minimum and maximum values ​​are structured in a percentage ratio. The conducted research made it possible to establish the share of energy costs for ensuring the specified throughput capacity of the oil pipeline in comparison with energy dissipative losses during oil transportation. It is shown that energy costs for maintaining the stress-deformed state of the pipeline are insignificant, and it is practically impossible to reduce them. The most significant are dissipative and inertial energy losses, the reduction of which will increase the energy efficiency of pipeline transport.